2015
DOI: 10.1016/j.ajpath.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Robust in Vitro Hepatitis B Virus Infection Model Using Fresh Human Hepatocytes Isolated from Humanized Mice

Abstract: The molecular mechanisms underlying the hepatitis B virus (HBV) life cycle are poorly understood because of the lack of appropriate in vitro infection models. Herein, we report a highly effective in vitro HBV infection system using fresh human hepatocytes (HHs) isolated from chimeric mice with humanized livers. After the inoculation of sera collected from HBV-infected chimeric mice or patients to HHs, we measured levels of HBV DNA, mRNA, covalently closed circular DNA, and viral protein expression in HHs. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 34 publications
5
114
1
Order By: Relevance
“…It was recently reported that HBV infection in freshly isolated primary human hepatocytes could spread during long term culture through production of infectious virions and reinfection of surrounding cells (41). As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…It was recently reported that HBV infection in freshly isolated primary human hepatocytes could spread during long term culture through production of infectious virions and reinfection of surrounding cells (41). As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Huh-7, Huh7.5.1, Huh7-25, LucNeo#2, HuSE2, and 293T cells, as well as primary human hepatocytes, were cultured as described previously (2,(18)(19)(20). Huh7.5.1 and LucNeo#2 cells were kindly provided by Francis Chisari at The Scripps Research Institute and Kunitada Shimotohno at National Center for Global Health and Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…HBV genotype C isolates were purchased from PhenixBio [17,18]. Informed consent from the patient was obtained by Prof. Yasuhito Tanaka, Nagoya City University, Japan.…”
Section: Hbv Infectionmentioning
confidence: 99%
“…One day after plating, HHs were incubated with 250 mL of 2% DMSO-supplemented hepatocyte clonal growth medium (dHCGM) containing the inoculum in the presence or absence of 4% polyethylene glycol (PEG) 8000 (Promega, Tokyo, Japan) [17].…”
Section: Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation